2017
DOI: 10.1016/j.neuroscience.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Parafascicular thalamic nucleus deep brain stimulation decreases NMDA receptor GluN1 subunit gene expression in the prefrontal cortex

Abstract: The rodent parafascicular nucleus (PFn) or the centromedian-parafascicular complex of primates is a posterior intralaminar nucleus of the thalamus related to cortical activation and maintenance of states of consciousness underlying attention, learning and memory. Deep brain stimulation (DBS) of the PFn has been proved to restore arousal and consciousness in humans and to enhance performance in learning and memory tasks in rats. The primary expected effect of PFn DBS is to induce plastic changes in target neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The neuromodulation of CM-Pf complex using deep brain stimulation for Tourette’s syndrome is also an emerging target for treatment 125 . The DBS of Pf may modulate cognitive functions by inducing molecular-level gene expression changes in the prefrontal cortex 126 . The sPf stimulations show dopamine release modulation in the inferior colliculus of rats and are suggested to be involved in the auditory processing deficits associated with Parkinson's 127 .…”
Section: Discussionmentioning
confidence: 99%
“…The neuromodulation of CM-Pf complex using deep brain stimulation for Tourette’s syndrome is also an emerging target for treatment 125 . The DBS of Pf may modulate cognitive functions by inducing molecular-level gene expression changes in the prefrontal cortex 126 . The sPf stimulations show dopamine release modulation in the inferior colliculus of rats and are suggested to be involved in the auditory processing deficits associated with Parkinson's 127 .…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 67 For instance, Nanda et al 68 showed that CM-DBS raises GABA levels in the striatum of awake rhesus monkeys. Furthermore, Fernández-Cabrera et al 69 showed that CM-DBS lowers pathological levels of glutamatergic activity in the prefrontal cortex in rats.…”
Section: The Intralaminar Thalamus As Target In Epilepsymentioning
confidence: 99%
“…Recently, DBS of the parafascicular thalamic nucleus has shown to affect NMDA receptor GluN1 subunit gene expression in the prefrontal cortex. [ 6 ] In this study, 20 naïve Wistar rats were stimulated for 20 min at 1 Hz cathodic square pulse trains of 500 ms and a current intensity ranging from 60 to 100 μA depending on the rats’ behavior (agitation, motor stereotypies, or other abnormal behavior were avoided). The results showed that parafascicular thalamic nucleus DBS induced a decrease in NMDAR GluN1 subunit gene expression in the cingulate and prelimbic cortices, but no significant differences were found in the density of NMDA or GABAB receptors.…”
Section: Preclinical Studiesmentioning
confidence: 99%